Role of enteral nutrition in pancreaticocolonic fistulas secondary to severe acute pancreatitis: A case report. Issue 49 (December 2017) - Cui, Binxin; Zhou, Lu; Khan, Samiullah; Cui, Jianmin; Liu, Wentian
Abstract: Rationale: Pancreaticocolonic fistula (PCF) is an exceedingly rare complication of severe acute pancreatitis (SAP) and has primarily been treated surgically, but a few reported cases are successfully treated with nonsurgical methods. Patient concerns: A 32-year-old male presented to our hospital with chief complaints of sharp and persistent left upper quadrant abdominal pain radiating to the back. Diagnoses: Computed tomography showed a pancreatic pseudocyst replacing a majority of the pancreatic parenchyma and PCF that formed between the pancreas and the colon. However, the final diagnosis of PCF was confirmed by drainage tube radiograph, which revealed extravasation of contrast from the tail of the pancreas into the colon. Interventions: A therapeutic strategy of enteral nutrition (EN) was applied. Outcomes: The patient responded well to the treatment. No complication and recurrence were reported during 2-year follow-up. Lessons: This case highlights the role of EN in the treatment of PCF secondary to SAP. To the best of our knowledge, this is the first case of PCF that treated successfully with EN, rather than surgical or endoscopic intervention.